Dampak Upah Minimum terhadap Probabilitas Keluar dari Sektor Formal - Tridiana, Clara; Widyawati, Diah (UI Scholars Hub, 2018)
The effectiveness of minimum wages is still debated, even though minimum wage regulation increases worker’s wages, yet it causes “disemployment effect”. This study aims to identify differences in minimum wages impact on probabilities out of formal sector for unskilled and skilled workers. The type of skill used is based on job classification. Using Sakernas data in August 2010 and 2015, probit regression was conducted to estimate minimum wages impact on probabilities out of formal sector on skilled and unskilled workers. Based on analysis, minimum wage on probability of exit from formal sector is higher for unskilled workers than skilled workers.